2008
DOI: 10.1007/s00066-008-1777-7
|View full text |Cite
|
Sign up to set email alerts
|

Amifostine Use in Radiation-Induced Kidney Damage

Abstract: Static kidney scintigraphy represents an objective and reproducible method to noninvasively investigate kidney function following irradiation. Amifostine produced a significant reduction in radiation-induced loss of renal function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 28 publications
(42 reference statements)
2
8
0
Order By: Relevance
“…In some experimental rat models, amifostine given prior to RT was found to confer functional and histopathological protection. 38 Similarly, there was a significant reduction in MDA and apoptosis with amifostine in our study. This might reflect the fact that the degenerative changes observed in the germinal epithelium may be associated with increased generation of ROS.…”
Section: Discussionsupporting
confidence: 73%
“…In some experimental rat models, amifostine given prior to RT was found to confer functional and histopathological protection. 38 Similarly, there was a significant reduction in MDA and apoptosis with amifostine in our study. This might reflect the fact that the degenerative changes observed in the germinal epithelium may be associated with increased generation of ROS.…”
Section: Discussionsupporting
confidence: 73%
“…Amifostine is an organic thiophosphate ester prodrug and must be activated by alkaline phosphatase to be converted into an active sulfhydryl compound 2009 (Kaldir et al, 2008;Levi et al, 2002). It has been shown that amifostine can ameliorate functional renal damage in rat kidneys (Caloglu et al, 2009;Rolleman et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…In an effort to find a way of reversing the irradiation damage, two agents were studied in a rat model of radia- tion nephropathy βC and WGO. Rats are suitable animals for experimental models to estimate renal impairment as they similar to human structure (Kaldir et al, 2008).…”
Section: Discussionmentioning
confidence: 99%